Sumbangan Wanita Dalam Bidang Tafsir: Sorotan Dari Zaman Awal Islam Hingga Abad Ke 18: Women’s Contribution in the Field of Quranic Interpretation: Anaylisis Since the Beginning of Islam Until the 18th Century - Muhammad, Maslina; Abdullah, Mustaffa; Abd Razzak, Monika@Munirah (Online Journal of Research in Islamic Studies, 2019)
The aims of this research is to identify and analyze the involvement of women in the field of Quranic interpretation since the beginning of Islam. Further study also have been made to determine and identify women’s contributions specifically in the production of interpretations. This study uses historical and complete textual analysis methods. It was conducted by library research by referring to academic articles, paper works, books and kitab that is relevant to this topic. Indirectly, the methods have given the author more understanding about the topic of research. The study showed that women’s involvement in the field of Quranic interpretation since the beginning of Islam proved the great contribution of women’s mufassir in line with the mufassirīn. This study also shown that the work of Zīb al-Tafāsīr is a proof that succeeded in putting Zīb al-Nisā ’as a name which has a significant contribution in the field of Quranic interpretation.